THE EFFICACY OF PHARMACOTHERAPY AND LIFESTYLE MODIFICATION IN CARDIOVASCULAR DISEASES - Rozimurotov Abbos Hamza oglu; Turniyazov Azamat Askarovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Cardiovascular diseases (CVDs) remain the leading cause of global morbidity and mortality. This article comprehensively reviews the synergistic efficacy of modern pharmacotherapy and structured lifestyle modification in the prevention and management of CVDs. While pharmacotherapy, including statins, antihypertensives, and antithrombotic agents, provides a cornerstone for controlling physiological risk factors, evidence demonstrates that lifestyle interventions targeting diet, physical activity, smoking cessation, and stress management are not merely adjunctive but foundational. The analysis concludes that the most significant reductions in cardiovascular events and mortality are achieved through a fully integrated approach, where evidence-based medication is combined with sustained, patient-centered lifestyle changes. This dual strategy addresses both the biochemical and behavioral origins of atherosclerosis, offering a holistic model for cardiovascular care.